Efektivitas CCTV dan Teknologi Pengawasan Tidak Langsung Dalam Meningkatkan Keamanan Lalu Lintas - Pasaribu, Alfredo Alusiyus Octavianus; Arief Surya Awangga; Batubara, Erikson Imanuel; Yana Herlingga (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
The use of Closed Circuit Television (CCTV) and indirect surveillance technology has become a key element in modern security strategies. This study aims to evaluate the effectiveness of CCTV in preventing security threats, focusing on its ability to reduce crime rates and provide legal evidence. Data indicates that the installation of CCTV can lower theft rates by up to 47.4%, making it a significant deterrent for criminals who are reluctant to act in monitored areas. CCTV not only serves as a preventive tool but also as a means of real-time monitoring, enabling swift responses to emergency situations. Advanced technologies, such as AI-based video analytics and motion detection, further enhance these systems' capabilities in identifying suspicious behavior and delivering automatic notifications to security personnel. Additionally, CCTV recordings serve as strong visual evidence in investigations, aiding authorities in identifying perpetrators and reconstructing the chronology of events.